1987
DOI: 10.1172/jci112830
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation in canine mucopolysaccharidosis I. Effects within the central nervous system.

Abstract: Five dogs with mucopolysaccharidosis I, a model of human Hurler/Scheie syndrome, were transplanted with marrow from phenotypically normal littermates at 5 mo of age. At 3 and 9 mo posttransplantation, biopsies of cerebral cortex, liver, and cerebrospinal fluid were obtained. The a-L-iduronidase levels in these tissues were 0.8-7.4, 26-45, and 6.3-14.9% of the paired donor tissues, respectively. Although iduronidase was present in relatively low levels in the recipients' brains and cerebrospinal fluid at both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…6 BMT in patients or in experimental animals can lead to correction of the enzyme defect, a decrease in abnormal lysosomes in soft tisssues, and in some cases stabilisation of the neurological status. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, while there is general agreement on the effectiveness of BMT for the treatment of liver, spleen or soft tissue disease, there is no consensus on whether it has a beneficial effect on the disease induced progressive deterioration of brain function. The outcome of the neurological manifestations appears to depend on the initial mental status, the age of the patient, the engraftment of the grafted bone marrow and the development of graft-versus-host diseases (GVHD).…”
Section: Introductionmentioning
confidence: 99%
“…6 BMT in patients or in experimental animals can lead to correction of the enzyme defect, a decrease in abnormal lysosomes in soft tisssues, and in some cases stabilisation of the neurological status. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, while there is general agreement on the effectiveness of BMT for the treatment of liver, spleen or soft tissue disease, there is no consensus on whether it has a beneficial effect on the disease induced progressive deterioration of brain function. The outcome of the neurological manifestations appears to depend on the initial mental status, the age of the patient, the engraftment of the grafted bone marrow and the development of graft-versus-host diseases (GVHD).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] We have used the dog to study gene transfer strategies for hematopoietic stem cell gene transfer, 5,6,20 given that, in contrast to nonhuman primates, there are many spontaneous canine disease models to study gene therapy, eg alpha-l-iduronidase deficiency, pyruvate kinase deficiency and various immunodeficiencies. 1,2,21 In previous studies we showed that GALV-pseudotype vectors increased gene transfer into human progenitor cells and baboon marrow repopulating cells in comparison to amphotropic vectors. 4,5,7 We, therefore, investigated whether GALV-pseudotype vectors would also increase gene transfer into canine marrow repopulating cells.…”
Section: Discussionmentioning
confidence: 98%
“…These models can be used to study the clinical effectiveness of gene therapy for genetic diseases such as metabolic (alpha-l-iduronidase deficiency) or hematologic (pyruvate kinase deficiency) disorders. 1,2 In contrast to recent reports in nonhuman primates, 3,4 gene transfer efficiencies in the dog have remained low. 5,6 In this study we have therefore tested whether techniques employed in the nonhuman primates would also result in improved gene transfer efficiencies in the dog.…”
Section: Introductionmentioning
confidence: 94%
“…Likewise, problems arise during the clinical application of gene therapy, such as difficulties in controlling the expression and localization of the enzyme, 77) and BMT is a potentially dangerous procedure. 79) Differences in the degree of improvement among LSD patients following treatment 70,78,[80][81][82][83] suggest the need for careful consultation prior to treatment. Enzyme replacement therapy (ERT) is the most advanced therapeutic for treating LSDs and has been applied to Gaucher disease, 61) Fabry disease, 62,63) Pompe disease, 84,85) and mucopolysaccharidosis I, 64) II 86) and VI.…”
Section: Treatment Of Lysosomal Storage Diseasesmentioning
confidence: 99%